Design of Process Flow for Dental Prosthesis Using The Concept of Additive Manufacturing - Dave, Marmik M; Kothari, Kartik D (International Journal of Computer Sciences and Engineering, 2019)
Additive manufacturing or 3D printing technology has been developing rapidly since the last 30 years, and it indicates excellent potential for future development. The promising future of this technology causes its significant impact on medical science. Currently, this technology is expensive; however, it is slowly becoming more affordable. 3-D printing has a huge potential to change the future of medical model production and prototyping, due to the beneficial products it can produce. 3-D printing is a revolutionary technology that can positively impact the work of medical professionals while enhancing the lives of others. The findings from the research reveal that digital and rapid prototyping are viable in reducing development time and improving prototype accuracy. Current research work describes about constructing dental implants, bridge, and crowns for damaged tooth using Additive manufacturing. Researchers have obtained a 50% reduction in the manufacturing time of the tooth implants as compared to the conventional manufacturing method. The selected material is biocompatible, and it can perform the desired operation without being affected by the chemical reaction. In addition to the reactiveness, authors have also taken into consideration the patient-specific design and pattern manufacturing. With the help of the digital X-ray one can obtain the precise dimensions of the tooth and the CAD software enables the transformation, further castable resin pattern developed through additive manufacturing aids in the final stage of casting.